EKSISTENSI PESANTREN ARRAHMAH CURUP, BENGKULU: Antara kemunduran dan kurangnya sikap disiplin santri - Tika Tika; Ifnaldi Nurmal; Wandi Syahindra (Al-Mau'izhoh, 2020)
An Islamic boarding school is known as an educational institution which teaches discipline, independence, responsibility, and an attitude that cares of environment and has high social values. Such an attitude cannot be naturally embedded without being preceded by existing rules. It is such a different thing as regards community's assumptions about the degree of students’ discipline at Ar-Rahmah boarding school of Curup. Their assumptions are declining and have an impact on the lack of public confidence in the existence of Ar-Rahmah as an institution that teaches discipline. In order to answer questions surrounding this issue, this study was carried out by using a qualitative approach according to its procedures. This study concluded that the factors of low discipline included students’ low awareness in implementing the rules applied in the Islamic boarding school, educators’ weak supervision in students’ activities, and appropriate punishments not applied when any of the students broke the rules. Keywords: existence, community’s interest, discipline attitude